Pemikiran Konsep Ekonomi Mark Blaug Dan Kaitannya Dengan Muatan IPAS Di Sekolah Dasar - Anuraga, Bayu Septian (Pena Edukasia, 2024)
The economic concept is a science that studies human behavior in allocating limited resources to meet their varied and developing needs. The basic economic concepts introduced by Mark Blaug, such as production, consumption, trade and money, can be adapted and taught to children in social studies content in elementary schools. Thus, the link between Mark Blaug's economic concepts and social studies content in elementary schools provides a strong foundation for developing children's understanding of economics and social life in general. This helps them prepare to better understand and participate in the complex society of the future. The method used in the 'Literature review begins with selecting a topic, then determining keywords to search for journals using Indonesian and English through several databases including Google Scholar and Publish On Perish. This search was limited to journals from 2007 to 2023. Based on several explanations put forward, the Independent Curriculum Natural and Social Sciences (IPAS) learning has a significant connection with economic concepts. Thus, the link between Mark Blaug's economic concepts and social studies content in elementary schools provides a strong foundation for developing children's understanding of economics and social life in general.